Strategy For Improving Education Quality in SMP Al-Islam Tenggulun Solokuro Lamongan - Kurniati Pudji Lestari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
This study aims to explore how the strategy to improve the quality of education in SMP AL-ISLAM Tenggulun Solokuro Lamongan. This study uses a qualitative approach to the type of descriptive research. This research uses interview, observation and documentation methods. The results of this study indicate that the quality of education in SMP AL-ISLAM Tenggulun Solokuro Lamongan in the academic field is realized with quality learning; supported by good and adequate learning facilities; adequate infrastructure. And the provision of superior classes for students who have more intelligence in the field of Tahfidz. At SMP AL-ISLAM Tenggulun Solokuro Lamongan, improving the quality of education uses the Total Quality Management strategy. The implementation of the Total Quality Management strategy is manifested in several education quality improvement programs. The education quality improvement program at SMP AL-ISLAM Tenggulun Solokuro Lamongan includes programs in the field of curriculum, programs in the field of student affairs, programs in the field of public relations, programs in the field of improving teacher quality. Keywords: Strategy, Improvement, Quality of Education